Problems of Learning Media in Indonesian Language Subject at SMA Negeri 6 Kota Gorontalo - Nur Aliyatun Mardha Salam; Sayama Malabar; Sitti Rachmi Masie (PT MEDIA JURNAL DAN PENDIDIKAN, 2026)
This study aimed to describe the problems of Indonesian language learning media at SMA Negeri 6 Kota Gorontalo, encompassing: (1) types of available and used media, (2) media condition and feasibility, (3) student perceptions, and (4) obstacles faced by the teacher. The study employed a descriptive design with a mixed methods approach of the sequential explanatory type, in which quantitative data collection and analysis were conducted first, followed by qualitative data to deepen and explain the quantitative results. Data were collected through a Likert-scale questionnaire (N=60 students), structured classroom observation, and semi-structured in-depth interviews. Quantitative analysis applied descriptive statistics (mean and percentage), while qualitative analysis employed the Miles and Huberman interactive model with source and technique triangulation. The results showed: (1) media used included LCD/projector, PowerPoint, textbooks, student worksheets (LKPD), internet applications, and sticky notes; (2) media condition was generally adequate with a mean quality score of 4.08 out of 5 (Good category), although internet accessibility scored only 3.12; (3) student perceptions were positive, with 95% of respondents in the Good and Very Good categories, and the learning effectiveness indicator averaged 4.26; and (4) the main obstacles were multidimensional, including unstable internet networks, limited devices, absence of a language laboratory, and minimal institutional policy. The study concludes that integrated solutions encompassing technical, pedagogical, and institutional aspects are necessary.